1961
DOI: 10.1136/jcp.14.6.622
|View full text |Cite
|
Sign up to set email alerts
|

The plasma clearance of injected doses of folic acid as an index of folic acid deficiency

Abstract: The folic acid clearance test of Chanarin (1958) has been studied in normal white subjects, patients with megaloblastic anaemia, healthy Bantu males, Bantu females, hospital patients without anaemia, and in patients with scurvy.The test clearly distinguishes patients with megaloblastic anaemia, where clearance from the plasma of injected folic acid is abnormally rapid, from normal subjects. The rate of clearance of folic acid is abnormally rapid both in vitamin B12and in folic acid deficiency. Rapid clearance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

1968
1968
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 16 publications
0
10
0
1
Order By: Relevance
“…The rapid rise in serum folate back to the control level between hours 28 and 32 in this subject was probably caused in part by an intravenous injection of 5 mg of folic acid' at the 30th h (arrow, Fig. 1), although with a half-life of approximately 15 min for intravenously injected folic acid (14,15), the great majority of this folic acid would have been cleared from the plasma within 2 h.…”
Section: Resultsmentioning
confidence: 99%
“…The rapid rise in serum folate back to the control level between hours 28 and 32 in this subject was probably caused in part by an intravenous injection of 5 mg of folic acid' at the 30th h (arrow, Fig. 1), although with a half-life of approximately 15 min for intravenously injected folic acid (14,15), the great majority of this folic acid would have been cleared from the plasma within 2 h.…”
Section: Resultsmentioning
confidence: 99%
“…One notable aspect of short-term kinetic studies involved the measurement of plasma folate clearance rate following an intravenous injection of folic acid (13,37,46,54). Chanarin et al (13) observed that the clearance rate of serum folate following folic acid injection (based on Streptococcus faecalis assays) was greater in vitamin B12-deficient megaloblastic anemia patients than in normal controls.…”
Section: Short-term Kineticsmentioning
confidence: 98%
“…10 Vitamin C has been shown to increase iron absorption two-to six-fold, and to prevent oxidation and excretion of folate. 13,14 In human experiments, vitamin C deficiency impaired vasoconstriction in response to adrenergic stimuli; this effect may underlie episodes of syncope, ST-segment elevation, and apparent sudden cardiac death. 15 The mechanism by which vitamin C deficiency causes other commonly described symptoms of scurvy, including fatigue, depression, and cardiovascular events, is less understood, but may reflect vitamin C's involvement in the metabolism of carnitine, corticosteroids, and neurotransmitters.…”
Section: Discussionmentioning
confidence: 99%